2019
DOI: 10.1038/s41467-019-11504-2
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a polygamous repressor reveals how phage-inducible chromosomal islands spread in nature

Abstract: Stl is a master repressor encoded by Staphylococcus aureus pathogenicity islands (SaPIs) that maintains integration of these elements in the bacterial chromosome. After infection or induction of a resident helper phage, SaPIs are de-repressed by specific interactions of phage proteins with Stl. SaPIs have evolved a fascinating mechanism to ensure their promiscuous transfer by targeting structurally unrelated proteins performing identically conserved functions for the phage. Here we decip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 44 publications
(77 reference statements)
5
27
0
Order By: Relevance
“…4A). We used this region because in all characterised SaPIs the Stl proteins bind to the region that lies between stl and str(5) (9) and our reporter assays showed as regulated by Stl. The detailed analysis of the protected regions identified 8 putative Stl binding sites, organised as 4 different putative operators (1-4) (Fig.…”
Section: The Sapi1 Stl-str Intergenic Region Contains 8 Stl Sapi1 Binding Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…4A). We used this region because in all characterised SaPIs the Stl proteins bind to the region that lies between stl and str(5) (9) and our reporter assays showed as regulated by Stl. The detailed analysis of the protected regions identified 8 putative Stl binding sites, organised as 4 different putative operators (1-4) (Fig.…”
Section: The Sapi1 Stl-str Intergenic Region Contains 8 Stl Sapi1 Binding Sitesmentioning
confidence: 99%
“…Thus, the inducers for SaPIbov1, SaPI1 or SaPI2 are the phage-encoded dUTPases, Sri or recombinase proteins, respectively (4)(5)(6). Because of the singularity of the induction-repression mechanism present in the SaPIs, and to gain more insight into this interesting system, we recently solved the structure of the SaPIbov1 Stl (Stl SaPIbov1 ) repressor alone and in complex with two different inducing proteins, the dimeric and trimeric dUTPase proteins encoded by phages O11 and f11, respectively (9). Our studies revealed that Stl SaPIbov1 is a canonical dimer, with a modular structural organisation reminiscent of that previously reported for many phage-and other MGE-encoded repressors, including the CI repressor from the archetypical phage l (9, 10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the inducers for SaPIbov1, SaPI1 or SaPI2 are the phage-encoded dUTPases, Sri or recombinase proteins, respectively ( 4–6 ). To gain more insight into this interesting and distinctive induction-repression mechanism of the SaPIs, we recently solved the structure of the SaPIbov1 Stl (Stl SaPIbov1 ) repressor alone and complexed with two different inducing proteins: the dimeric and trimeric dUTPase proteins of phages O11 and ϕ11, respectively ( 9 ). Our studies revealed that Stl SaPIbov1 is a canonical dimer, with a modular structural organization reminiscent of many well-studied phage and MGE repressors, including the CI repressor of archetypical phage λ ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…To gain more insight into this interesting and distinctive induction-repression mechanism of the SaPIs, we recently solved the structure of the SaPIbov1 Stl (Stl SaPIbov1 ) repressor alone and complexed with two different inducing proteins: the dimeric and trimeric dUTPase proteins of phages O11 and ϕ11, respectively ( 9 ). Our studies revealed that Stl SaPIbov1 is a canonical dimer, with a modular structural organization reminiscent of many well-studied phage and MGE repressors, including the CI repressor of archetypical phage λ ( 9 , 10 ). These repressors have N-terminal domains that recognize and bind to their cognate DNA operator regions, and C-terminal domains that are involved in repressor dimerization and inducer recognition.…”
Section: Introductionmentioning
confidence: 99%